2017
DOI: 10.3340/jkns.2016.0102.001
|View full text |Cite
|
Sign up to set email alerts
|

The Use of MR Perfusion Imaging in the Evaluation of Tumor Progression in Gliomas

Abstract: ObjectiveDiagnosing tumor progression and pseudoprogression remains challenging for many clinicians. Accurate recognition of these findings remains paramount given necessity of prompt treatment. However, no consensus has been reached on the optimal technique to discriminate tumor progression. We sought to investigate the role of magnetic resonance perfusion (MRP) to evaluate tumor progression in glioma patients.MethodsAn institutional retrospective review of glioma patients undergoing MRP with concurrent clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…PsP is more frequent in patients treated with concomitant temozolomide than in those receiving radiation therapy alone and is particularly frequent in patients with O6‐methylguanine‐DNA methyltransferase ( MGMT ) promoter methylation (MGMT_MET) . In spite of new and promising advanced MRI and PET‐based techniques , PsP remains indistinguishable from early progression (eP). Since a final diagnosis can only be reached through histopathological verification or subsequent MRIs, PsP can confound treatment monitoring, with direct consequences in clinical practice, as it can lead to prematurely withholding adjuvant temozolomide or to overestimating the efficacy of a second‐line therapy.…”
Section: Introductionmentioning
confidence: 99%
“…PsP is more frequent in patients treated with concomitant temozolomide than in those receiving radiation therapy alone and is particularly frequent in patients with O6‐methylguanine‐DNA methyltransferase ( MGMT ) promoter methylation (MGMT_MET) . In spite of new and promising advanced MRI and PET‐based techniques , PsP remains indistinguishable from early progression (eP). Since a final diagnosis can only be reached through histopathological verification or subsequent MRIs, PsP can confound treatment monitoring, with direct consequences in clinical practice, as it can lead to prematurely withholding adjuvant temozolomide or to overestimating the efficacy of a second‐line therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Ozsunar et al obtained similar sensitivity and specificity of 86% and 70% respectively, though they did manage to reach significance in their results (p < 0.01) [31]. A more recent publication by Snelling et al [36] in turn found a sensitivity of 60.8% and specificity of 87.8% using a purely qualitative method. and 12 for each of these parameters respectively.…”
Section: Dynamic Susceptibility Contrast (Dsc) Mrimentioning
confidence: 90%
“…Two publications looked at parameters from the SI-time curve including relative peak height (rPH) and percentage signal recovery (rPSR) [16] [39]. There were 3 studies that performed qualitative analysis using maps obtained from DSC-MRI [19] [31] [36].…”
Section: Dynamic Susceptibility Contrast (Dsc) Mrimentioning
confidence: 99%
“…The vascular pathology of low-grade glioma states that tumor vessels are mainly formed of normal endothelial cells, with cell-to-cell tight junction and relatively intact blood-brain barrier resulting in decreased blood flow and blood volume parameters in perfusion MRI techniques [3]. Most of the previous studies differentiating high-grade glioma from low-grade glioma by perfusion MRI techniques revealed low perfusion parameters in low-grade glioma patients [15,16]. In our study, 9 out of 14 low-grade glioma patients showed hypoperfusion in ASL-CBF comparable to DSC-PI, while four cases showed hyperperfusion on ASL, three of which were hypoperfused on DSC-PI.…”
Section: Discussionmentioning
confidence: 99%